Developing a Framework and Process of Targeted Innovation - Pun, Tsz Ching Audris (2014)
Today, innovation is important to companies and to economies as innovation drives performance and economic growth. Many companies have followed conventional innovation processes, such as structured innovation process and systematic innovation process, and have achieved great success, especially in the field of new product development; however, these processes are often time consuming and require a lot of resources, rending them not suitable for small and medium sized enterprises (SMEs). Thus, this dissertation aims to come up with a new framework for innovation that is suitable for SMEs. It aims to shorten the conventional innovation process, as well as to ensure high success rate even with limited resources available.